Water management toward regenerative wineries - Oliveira, Margarida (2022)
Wine producers are now fully aware of the water-energy nexus, given the challenges created by climate change. By identifying potential environmental impacts of the wine industry, related to water and fossil energy use, wineries are taking action to improve their performance. This chapter reviews a set of technologies and strategies that can lead wineries to implement a regenerative approach, minimizing resources, recovering value from wastewater/waste, and replacing fossil energy with renewable sources. The approach is illustrated by presenting four case studies, located in three Mediterranean countries (France, Italy, and Portugal). The main conclusions are: (1) water and energy consumption ratios vary according to the wine type; (2) wastewater treatment systems tend to close the water cycle in countries facing severe water scarcity; and (3) the adoption of renewable energy in wineries is a reality today, but the adopted renewable energy depends on the region where it is located.